2015
DOI: 10.1016/j.virol.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley fever virus NSS gene expression correlates with a defect in nuclear mRNA export

Abstract: We investigated the localization of host mRNA during Rift Valley fever virus (RVFV) infection. Fluorescence in situ hybridization revealed that infection with RVFV altered the localization of host mRNA. mRNA accumulated in the nuclei of RVFV-infected but not mock-infected cells. Further, overexpression of the NSS gene, but not the N, GN or NSM genes correlated with mRNA nuclear accumulation. Nuclear accumulation of host mRNA was not observed in cells infected with a strain of RVFV lacking the gene encoding NSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…Copeland et al . previously showed that there is a defect in mRNA export in RVFV-infected cells, and this export defect correlates with NSs gene expression 46 . Their work demonstrated that host mRNA was localized to the nucleus of infected cells when compared to mock-infected cells, and that NSs is responsible for this phenomenon.…”
Section: Resultsmentioning
confidence: 91%
“…Copeland et al . previously showed that there is a defect in mRNA export in RVFV-infected cells, and this export defect correlates with NSs gene expression 46 . Their work demonstrated that host mRNA was localized to the nucleus of infected cells when compared to mock-infected cells, and that NSs is responsible for this phenomenon.…”
Section: Resultsmentioning
confidence: 91%
“…The interaction with TFIIH-p62 thereby depends on a ΩXaV motif (where Ω: aromatic, X: any, a: acidic, V: valine) located in the C-terminal region of RVFV NSs [ 124 ]. Moreover, a nuclear mRNA export block was observed in RVFV NSs-expressing cells [ 125 ]. In contrast to these broadly-acting host cell shutoff mechanisms, RVFV NSs was also reported to specifically inhibit IFN induction by recruiting a transcriptional suppressor complex containing Sin3A associated protein 30 (SAP30) to the IFN-β promoter [ 126 ].…”
Section: Viral Countermeasuresmentioning
confidence: 99%
“…Within the Phenuiviridae family, the IFN antagonistic functions of the non-structural (NSs) proteins of Rift Valley Fever Virus (RVFV) and Uukuniemi virus (UUKV) have been extensively studied and reviewed [97][98][99]. RVFV NSs localizes to the nucleus where it directly inhibits IFN-β promoter activity, and directly prevents the export of host mRNA to the cytoplasm [100,101]. UUKV has not been shown to cause disease in humans; UUKV NSs has weak IFN antagonism activity through its interaction with MAVS [98,99].…”
Section: Innate Immune Evasion By Interferon-antagonistic Function Ofmentioning
confidence: 99%